A Comprehensive Structural Study Of Kati Kasheruka And It’s Applied Aspects W.S.R. To Katishool In Lumbar Spondylosis - Desurkar, Bharat N; Patil, Mahesh R; Giritammanavar, J T; Butali, Kavita; Mohan, G Vinay (International Research Journal of Ayurveda & Yoga, 2020)
Ayurveda adapts laws of nature and propounds number of applied doctrines for the understanding of life, health and diseases. Human lumbar vertebrae supports the weight of the upper body. Loads lifted and carried by the upper extremities cause significant loading and stress to the vertebral bodies. Katishool can be a result of conditions affecting the discs between the vertebrae, ligaments around the spine and discs, spinal cord and nerves, muscles of lower back and various other factors. Increasing age brings about inevitable changes in the structure, shape and function of the human vertebrae.. What factors mediate this degenerative progression in lumbar spine? What leads a large portion of the population to manifest spondylosis, even early on their lives? Hence the conclusion’s put forth are that the Ruja, Stambha, Khanjata, Shopha, Asthi vikruthi lakshana’s are seen in the Kati Sandhi during trauma ,sports, routine work injuries are due to the involvement of structural changes in lumbar vertebrae which were identified by the radiological findings..Vata dosha is the major factor behind the whole pathogenesis involved in Katishoola. All the Nidanas of Vatavyadhi & Vata prakopa can be regarded as Nidana of Katishoola..Degenerative changes are more likely to occur in women as compared to men.